2006
DOI: 10.1108/14676370610655904
|View full text |Cite
|
Sign up to set email alerts
|

As green as we think? The case of the College of Charleston green building initiative

Abstract: Purpose -This paper seeks to disseminate knowledge regarding the experiences of a student team in implementing a campus-level sustainability initiative, outlining the strategy to measure the potential impact of this initiative. Design/methodology/approach -Project design is a case study. Via interviewing and surveys, the study observed student and faculty attitudes, information levels and behaviors regarding sustainability both before and after project implementation. Calculated sustainability scores were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 19 publications
1
37
0
1
Order By: Relevance
“…In order to overcome these constraints, Levy and Dilwali [26] suggest the creation of communication networks promoting the flow of information regarding pre-existing or proposed environmental management initiatives. Alternative solutions are the implementation of seminars for educational purposes and briefings on the progress of environmental management initiatives in the institution [19,33].…”
Section: Information and Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome these constraints, Levy and Dilwali [26] suggest the creation of communication networks promoting the flow of information regarding pre-existing or proposed environmental management initiatives. Alternative solutions are the implementation of seminars for educational purposes and briefings on the progress of environmental management initiatives in the institution [19,33].…”
Section: Information and Knowledgementioning
confidence: 99%
“…A third way of promoting sustainability through HEIs derives from their important role in transmitting knowledge to society [19]. In particular, the involvement of citizens in university activities or through research programs which improve the natural environment of the local community may be regarded as alternative contributions to the promotion of sustainable development through HEIs [20].…”
Section: Introductionmentioning
confidence: 99%
“…Owens and Halfacre-Hitchcock (2006) reported that several researchers acknowledged the positive role of HEIs in promoting sustainability through such program. In Malaysia, several universities such as UKM, UM, Universiti Sains Malaysia (USM), Universiti Teknologi Malaysia (UTM), and Universiti Putra Malaysia (UPM) have a similar program.…”
Section: Sustainability In Practice (Other Than the Formal Curricula)mentioning
confidence: 99%
“…The rationale is that the concept of sustainability presents diverging interpretations according to the actors that are inferred [7]. Some have a master plan, environmental plan, guidelines, or statement about being sustainable campus [6]; some by signing of national or international declarations [8]; and others create individual institutional policies or framework to achieve campus sustainability, such as ISO 14001 [9 -11], eco-management and audit scheme (EMAS) [12], green building initiative [13], environmental impact assessment [14], graphical assessment of sustainability in universities (GASU) [15,16], sustainability tracking, assessment and rating system (STARS) [17,18], and Alshuwaikat and Abubakar's framework [2,19,20].…”
Section: Introductionmentioning
confidence: 99%